Quality of Life Among Cardiac Patients Following a Cardiac Rehabilitation Programme at a Heart Centre in Malaysia - Chau Chung, Chai; Be Kim, Leong; Lin Kiat, Liew; Joanna Varuges, Abraham; Sing Kok, Bong; Sriganes, Nachimuthu (Hong Kong College of Cardiology, 2025)
Objectives: Cardiovascular disease is a significant cause of morbidity and mortality in Malaysia, negatively impacting the quality of life (QoL) of cardiac patients. There have been limited local studies on QoL among cardiac patients following cardiac rehabilitation programmes (CRP) in Malaysia. This study aimed to study QoL among cardiac patients following CRP and identify barriers to QoL improvement at Sarawak Heart Centre, Malaysia.